Reduced white matter integrity in amateur boxers - Herweh, Christian; Hess, Klaus; Meyding-Lamadé, Uta; Bartsch, Andreas J.; Stippich, Christoph; Jost, Joachim; Friedmann-Bette, Birgit; Heiland, Sabine; Bendszus, Martin; Hähnel, Stefan (Neuroradiology, 2016)
Professional boxing can lead to chronic traumatic encephalopathy, a variant of traumatic brain injury (TBI). Its occurrence in amateur boxers is a matter of debate since amateur boxing is considered to be less harmful due to more strict regulations. However, several studies using different methodological approaches have revealed subtle signs of TBI even in amateurs. Diffusion tensor imaging (DTI) is sensitive to microscopic white matter changes and has been proven useful in TBI when routine MR imaging often is unrevealing.
Gesehen am 13.05.2020